Modification of reconstruction of left ventricular outflow tract, aortic root and the intervalvular fibrous body for extensive infective endocarditis: a single-centre experience. (19th May 2022) - El-Sayed Ahmad, Ali; Salamate, Saad; Amer, Mohamed; Abdullaahi, Abdisalan; Bayram, Ali; Sirat, Sami; Bakhtiary, Farhad
Abstract: OBJECTIVES: Extensive infective endocarditis (IE) stays a serious life-threatening disease with high mortality and morbidity. The aim of this study is to analyse our experience with our modified surgical technique for extensive IE during the last 4 years. METHODS: Between March 2017 and February 2021, all patients with extensive IE required our modified technique consisting of a radical surgical resection of all infected cardiac tissues, the replacement of infected valves and a reconstruction of the intervalvular fibrous body, the aortic root and the left ventricular outflow tract with modified elephant trunk were included in this study. RESULTS: Our modified technique was performed on 41 patients during the study period. The age median was 74 [interquartile range (IQR): 66.5–76.5] and 61.0% ( n  = 25) were female. Thirty-three patients (80.5%) were in New York Heart Association Class III–IV and 7 patients (17.1%) in cardiogenic shock. The median logistic European system for cardiac operative risk evaluation II as predicted risk of mortality was 35% (IQR: 28–78%). The median cardiopulmonary bypass time and cross-clamping time were 126 (IQR: 86.5–191) and 78 (IQR: 55.5–108) min, respectively. Intraoperative mortality and 30-day mortality were 4.8% (2 patients) and 19.5% (8 patients), respectively. Low cardiac output with necessity for mechanical support, stroke and new renal dialysis developed in 9.8% (4 patients), 17.1% (7 patients) and 22.0% (9 patients), respectively. New pacemaker implantation was noted in 39.0% (16 patients). Intensive care stay and hospital stay had medians of 6 (IQR: 5–12) and 14 (IQR: 12.5–20.5) days, respectively. One-year mortality and 4-year mortality were 34.1% (14 patients) and 39.0% (16 patients), respectively. Kaplan–Meier survival estimates were 60.3% (95% confidence interval: 46.2–78.6%) at 3 years. CONCLUSIONS: Our modified technique can be performed in patients with extensive IE with acceptable early and mid-term morbidity and mortality. We believe that this technique is an available option for this ill-fated group of patients. Abstract : Infective endocarditis (IE) is a life-threatening condition affecting 3–15 patients per 100, 000 with a high morbidity and mortality [1–3].